PERAN BRAND AWARENESS MEMEDIASI PENGARUH VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN - Rahayu, Ni Luh Putu Gangga; Kusumadewi, Ni Made Wulandari (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023, 2023)
This study aims to examine and explain the role of brand awareness in mediating the influence of viral marketing on purchasing decisions. This research was conducted in Denpasar City. The population of this study is all people in Denpasar City who consume and buy Lemonilo instant noodle products and know the viral marketing of Lemonilo instant noodles. The number of samples used is as many as 120 respondents with non-probability sampling technique, especially purposive sampling method. Data collection in this study was carried out using a questionnaire method which was distributed online by the researcher with the help of a google form. The data analysis technique used is path analysis to analyze the pattern of relationships between variables and using the Sobel test to determine the role of mediating variables. The results of the analysis and discussion of this study found that viral marketing has a positive and significant effect on purchasing decisions, viral marketing has a positive and significant effect on brand awareness, brand awareness has a positive and significant effect on purchasing decisions, and brand awareness mediates the influence of viral marketing on purchasing decisions.